Utilization of sunflower (Helianthus annuus) heads as roughage source in complete diets - MOHAN, A MADAN; RADDY, G V N; REDDY, M R (The Indian Journal of Animal Sciences, 2013)
Two complete diets containing (i) 40% ground sunflower heads and (ii) 20% ground flower heads + 20% lucerne hay, were compared with a cpnventional diet containing concentrate mixture and chopped sorghum straw fed separately by feeding to 3 permanently fistulated crossbred bulls in digestion and metabolism experiments using 3 x 3 latin square. Organic matter, NFE (P